Physicians’ clinical experience and perspectives following a pilot, blended learning, point of care ultrasound course in Ghana- a mixed methods analysis - Pathak, A; Limbani, F; Awuku, YA; Booth, A; Joekes, E (BioMed Central, 2024)
Background: Point of Care ultrasound (POCUS) is rapidly gaining popularity in resource constrained settings. Optimising training is important to ensure safe and effective implementation. To expand POCUS expertise in Ghana, we co-developed and piloted a context specific, multi-disciplinary, blended learning programme, targeted at physicians of any grade or speciality providing acute care in the public health sector. In this retrospective mixed method study, we capture the “real world” experience of participants, using POCUS in their daily practice, as well as the barriers and enablers they perceived to implementation. Results: Eight emergency and internal medicine specialists and residents participated, working across three teaching hospitals, treating both general and specialist patients. They implemented each POCUS application taught, with cardiac indications, inferior vena cava (IVC) assessment, deep venous thrombosis (DVT) diagnosis, lung/pleural assessment and peripheral vascular access being most frequent at 3–6 times/week. An estimated 40% of patients could not have afforded any other diagnostic tests. They considered the pilot curriculum adequate for general practice and the majority of applications of low difficulty (71%). For cases sent for second opinion, they are self-reported that their findings were confirmed in 60–78% of cases. Perceptions about the relative advantage of POCUS over the usual approaches to diagnosing patients enabled implementation. Generally, they believed that POCUS improved their clinical decision making and that more certified training courses need to be run at lower cost to make them more accessible. All participants valued ongoing connections after training to ask for help and consolidate their skills. Continued evaluation and reflection on their POCUS practice to improve quality was unanimously reported as important, yet none had a formal system for this. The strongest barrier was access to equipment and maintenance. A lack of training opportunities and local mentors, and negative beliefs from other departments and hospital administration were further barriers. Conclusion: Our new blended learning curriculum met the needs of physicians caring for patients with general and specialist presentations, with strong reported positive experience of improved bedside diagnostic capabilities, especially for the large proportion of patients unable to afford or access alternative diagnostic tests. Their experience drives the need for further training and for solutions to current barriers of equipment availability, training costs and lack of quality assurance mechanisms.